HACCP operation in two Latin American meat packers: Case study - N. M. Guerrero-Castiblanco; E. Maldonado-Simán; P. A. Martínez-Hernández (Теория и практика переработки мяса, 2024)
The hazard analysis and critical control point (HACCP) system is a protocol aimed to guarantee food safety, especially in companies dedicated to meat processing. Companies in food international trade are subjected to intense inspection and verification processes, and international standard certifications have become a key factor in global trade. The purpose of this study was a comparative analysis of HACCP certification in the Mexican and Chilean meat packers that send meat to international markets by a field inspection of each to identify opportunities for improvement. International trade standards along with packers’ expectations and needs to be fulfilled to attain a place in world markets were bases for this study. Guidelines for field inspection came from the HACCP protocol. Field data were derived from 15 indicators —  five intrinsic to the HACCP plan and ten external. The Chilean packer was superior to the Mexican packer in terms of many indicators. Thus, the first one had a chance for a better position in international markets than the latter. It was concluded that the HACCP audit is an excellent tool to measure the suitability of meat packers in achieving a place as a supplier and remaining in the international food trade.